Analysis of the Use of Guidebooks on Student Learning Outcomes in Fiqh Subjects at Mts Negeri 2 Bungo - Rahayu Saputri; Andryadi Andryadi; Mabruri Mabruri (Yayasan Adra Karima Hubbi, 2026)
The use of guidebooks in Fiqh learning at MTs Negeri 2 Bungo is an important issue because even though it is available and used, its function as an independent learning resource is not optimal. This study aims to analyze the use of guidebooks on student learning outcomes and identify factors that affect their effectiveness. With a qualitative approach and case study design, data were collected through interviews, observations, and documentation involving Fiqh teachers, students, and deputy heads of madrasas in curriculum areas. The results of the study showed that handbooks support the delivery of learning materials and exercises, but their use is still dominant in the classroom and has not yet functioned as an independent reference. Its effectiveness is influenced by student involvement, language readability, design quality, content contextuality, teacher strategies, and madrasah support in building a learning culture. Students who actively use books tend to have a better understanding, although the influence is uneven. Different from previous studies that emphasized statistical relationships between variables, this study highlights the interaction between students, teachers, teaching materials, and the learning environment. The findings confirm that the optimization of guidebooks requires student-centered learning strategies, the development of communicative and contextual teaching materials, and consistent literacy habituation.